Not All T Cell Synapses Are Built the Same Way. Issue 11 (November 2019) - Kumari, Sudha; Colin-York, Huw; Irvine, Darrell J.; Fritzsche, Marco
Abstract : T cells comprise functionally diverse subtypes. Although activated via a conserved scheme of antigen recognition by their T cell receptor, they elicit heterogeneous activation and effector responses. Such functional diversity has been appreciated in gene expression studies, functional assays, and disease models. Yet, our understanding of the principles underlying T cell subtype-specific activation and antigen recognition in the immunological synapse remains limited. This is primarily due to difficulties in primary T cell visualization at high spatiotemporal resolution and the adoption of tractable transformed T cell systems for cell biological experiments that may not correctly represent primary T cell constitutional diversity. Here, we discuss recent findings regarding the architectural and dynamic diversity of the immunological synapse and state-of-the-art methodologies that can be utilized to provide clues on how biological and biophysical differences in synaptic make-up could govern functional divergences in T cell subtypes.